تطبيقات قاعدتي "درء المفاسد مقدم على جلب المصالح " و"الضرورات تبيح المحظورات" على الجراحة التجميليةة : تطبيقات قاعدتي “درء املفاسد مقدم على جلب املصاحل” و “الضرورات تبيح احملظورات” على اجلراحة التجميلية - سعيدة عكسه; حياة كتاب (الدراسات الإسلامية, 2023)
This research addresses a significant contemporary discourse regarding the influence of Shari‘ah maxims on medical matters, particularly those about accidents and more specifically medical interventions on the human body. While such interventions are not novel, teeth implants are considered an ancient practice. However, advancements in medical science have enabled a considerable enhancement in altering, removing, or correcting organ structures, commonly called plastic surgeries. This study seeks to elucidate the application of certain Shari‘ah maxims to cosmetic surgeries, specifically those encapsulated in the maxims of "Repelling evil supersedes securing benefits" and the maxim "Necessities relax prohibitions”. The Study aims to underscore the execution of these maxims in the realm of cosmetic surgeries, delineating their impact and benefits, and emphasising the imperative consideration of these maxims by medical practitioners and their clientele before undertaking such procedures.